Proyecto de Vida de las Mujeres Indígenas de la Cultura Wayuu – Guajira-Colombia 2021 (2021)
This paper aims to describe the life project of the Wayuu women of La Guajira, showing relevant aspects regarding the establishment and development of the life project, providing information for the understanding of the dynamics of women in this population, the approach for this research is humanism within which the author is taken as a reference D'Angelo's knowledge or theory is centered on an integral holistic approach, since within the individual it is important to take into account his social environment.